2013
DOI: 10.1016/j.ijdevneu.2013.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Morphine‐enhanced apoptosis in selective brain regions of neonatal rats

Abstract: Prolonged neonatal opioid exposure has been associated with: antinociceptive tolerance, long-term neurodevelopmental delay, cognitive, and motor impairment. Morphine has also been shown to induce apoptotic cell death in vitro studies, but its in-vivo effect in developing rat brain is unknown. Thus, we hypothesized that prolongued morphine administration in neonatal rats in a model of antinociceptive tolerance and dependence is associated with increased neuroapoptosis. We analyzed neonatal rats from the followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 99 publications
6
66
0
Order By: Relevance
“…However, when the postnatal morphine administration was followed by 4 days of abstinence, the pain reaction increased significantly (Zissen et al, 2006). Similarly, antinociceptive tolerance to morphine administration developed, as measured by a hot plate test (Bajic et al, 2013). In these cases, brain region-specific apoptosis occurred in unaffected glial cells, serving as a possible background mechanism (Bajic et al, 2013).…”
Section: Experimental Conditions In Rodentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the postnatal morphine administration was followed by 4 days of abstinence, the pain reaction increased significantly (Zissen et al, 2006). Similarly, antinociceptive tolerance to morphine administration developed, as measured by a hot plate test (Bajic et al, 2013). In these cases, brain region-specific apoptosis occurred in unaffected glial cells, serving as a possible background mechanism (Bajic et al, 2013).…”
Section: Experimental Conditions In Rodentsmentioning
confidence: 99%
“…Similarly, antinociceptive tolerance to morphine administration developed, as measured by a hot plate test (Bajic et al, 2013). In these cases, brain region-specific apoptosis occurred in unaffected glial cells, serving as a possible background mechanism (Bajic et al, 2013).…”
Section: Experimental Conditions In Rodentsmentioning
confidence: 99%
“…Studies in neonatal rats have found increased neuroapoptosis and impaired cognitive functioning after exposure to pain and opioids [6,7,8]. However, these effects mainly occurred in response to an induced chronic inflammatory response - not necessarily mimicking the human situation.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Similarly, studies have described alterations in the development of the central nervous system in rats exposed to postnatal opiates. 15 Less is known about the potential effects of early exposure to antipsychotic agents, although there is extensive research on long-term exposure in children and adults and the development of the metabolic syndrome. 16 With short-term use, there have been theoretical concerns regarding QTc prolongation and neuroleptic malignant syndrome, as well as anticholinergic and hypotensive effects.…”
Section: Discussionmentioning
confidence: 99%